The Relationship between Environmental Factors and Nutritional Status on Malaria Incidence in Woyla District, West Aceh Regency - Hasrah Junaidi; Zakiyuddin Zakiyuddin; Enda Silvia Putri; Fitrah Reynaldi; Kiswanto Kiswanto (Journal of Nutrition Science, 2021)
Malaria is one of the main causes of death in many developing countries, which until now is still spread in the tropics and subtropics. This study aims to determine the relationship between environmental factors and nutritional status with the incidence of malaria in the Kuala Bhee Health Center Work Area, West Aceh Regency.This study uses a case control or retrospective study design. The case group was recorded as malaria patients based on registration data at the Kuala Bhee Health Center, Woyla District, Aceh Regency and resided in the working area of the Kuala Bhee Health Center, Woyla District, West Aceh Regency, while the controls were all people who were declared free of malaria.The results showed that the presence of livestock cages and the presence of standing water had a significant relationship with the incidence of malaria.It is recommended to the public to avoid activities outside the home at night by reducing the frequency of going out or not leaving the house during active hours of biting malaria vector mosquitoes, cleaning livestock cages and eliminating puddles around their homes.